The Thrust of Demand: Literary Writing and Cultural Democratization in Argentina, 1900-1930 - Rogers, Geraldine (2013)
This article focuses on ordinary people's interest in writing and publishing their texts during the first decades of the twentieth century in Argentina. In that period, the demand for participation and self-representation through literary writing founded an auspicious ground in newspapers and magazines "for the people", which had sections devoted to publishing or commenting on the works of readers. This article focuses on the emerging aspirations of a broad readership that was willing to exercise a right to the word, the way in which these demands found a place to be expressed, and how they were read and processed in different areas of the cultural field: the cultural market, left-wing culture and professional writers.